Pengaruh Pengaruh Kepuasan Pelanggan dan Customer Complaint Terhadap Pendapatan Limbah dan Irigasi PT. Pengembangan Pariwisata Indonesia (Persero) - Budiarta, Kadek; Budiasa, Gede Sujana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 10. Oktober 2017(pp.1868-2102), 2017)
This study aims to analyze the effect of customer satisfaction and customer complaints on waste and irrigation income PT. Development of Tourism Indonesia (Persero) as well as to analyze the effect of customer satisfaction on waste and irrigation revenue through customer complain at PT. Tourism Development of Indonesia (Persero). Data used primary data. The selected sample is 40 customers who use waste treatment and irrigation service of PT. Tourism Development Indonesia. The analysis technique used is Structural Equation Model (SEM) analysis. The result shows that customer satisfaction is not significant to waste and irrigation income. The variable of customer satisfaction turned out to have a positive and significant impact on customer complaint. Customer complaint variable has positive and significant impact on waste and irrigation income. customer complaint is a latent variable that proves to function as a mediator for customer satisfaction constructs.